PENGARUH ANALISIS FIXED SAMPLE SIZED SAMPLING, STOP OR GO SAMPLING, DAN DISCOVERY SAMPLING TERHADAP TINGKAT EFEKTIVITAS SISTEM PENGENDALIAN INTERN ATAS AKTIVITAS PEMBUATAN AKTA FIDUSIA DAN WAARMERKING PADA KANTOR NOTARIS DEWI MEUTIA KOTA PROBOLINGGO - Mutimmah Rustianawati; Febri Yanti Dwita (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2018)
This research aims to determine the level of effectiveness the company's internal control system if measured by using the analysis of Fixed Sample Sized Sampling, Stop Or Go Sampling, and Discovery Sampling. The subject of this research is Kantor Notaris of DewiMeutiaCiptaNingrum, S.H., M.H., M.Kn which used as research sample. This research data is obtained from direct observation of the transaction evidence that has been selected by using purposive sampling with certain criteria. The analysis technique used is quantitative descriptive technique. The steps of data analysis techniques used in this study is to calculate the effectiveness level of internal control system using Fixed Sample Sized Sampling, calculate the effectiveness of internal control system using Stop Or Go Sampling, and calculate the effectiveness level of internal control system using the Discovery Sampling testing procedure. The result of data processing shows that Internal Control System of DewiMeutiaProbolinggo Notary Office is considered effective.